112k views
0 votes
Someone just to help me solve this equation but I didn't quite understand can someone re-explain​

Someone just to help me solve this equation but I didn't quite understand can someone-example-1
User MCL
by
5.7k points

2 Answers

5 votes

Answer:

x=-2

y=-5

z=3

Explanation:

Ok so first you have to solve for x because its the easiest equation 3x=-6.

Divide by 3 on both sides and you get x=-2. Now that you have your x value you can plug that in to the second equation x+3y=-17. Making it -2+3y=-17. Solve for y by adding 2 to both sides making it 3y=-15 and then divide by 3 making it y=-5. Since you have your x and y value, you can plug that in to the top equation which is 4x-3y+6z=25 and making it 4(-2)-3(-5)+6z=25,

4(-2)-3(-5) equals 7 making your equation 7+6z=25. Take away 7 from both sides and you are left with 6z=18. 18/6 is 3 so you get z=3. Making your final answer: x=-2 y=-5 and z=3

Hope this helped.

User Hermann Schwarz
by
5.2k points
7 votes

Answer:

x = -2, y = -5, z = 3

Explanation:

You have to substitute the letter with its real value;

3x = -6

Divide both sides by 3;

x = -2

So now we have to replace x with -2;

x + 3y = -7

-2 + 3y = -17

Add 2 to both sides;

3y = -15

Divide both sides by 3;

y = -5

For the last equation you have to replace x and y since we have the values;

4(-2) - 3(-5) + 6z = 25

-8 + 15 + 6z = 25

7 + 6z = 25

Subtract 7 from both sides;

6z = 18

Divide both sides by 6;

z = 3

Check:

4(-2) - 3(-5) + 6(3) = 25

-8 + 15 + 18

7 + 18 = 25

25 = 25

This mean the values are correct.

User NobodysNightmare
by
5.1k points